ACTIVATION OF STUDENT RESOURCES REGARDING THE WORK-ENERGY THEOREM - Adisna, Qowiyyun Dyaheksita Pradani Putri; Sutopo, Sutopo; Khusaini, Khusaini (Jurnal Pendidikan Matematika dan IPA, 2024)
Students' understanding of physics will increase along with learning during lectures, but thoughts on this understanding can be flexible and not always permanent, so it is necessary to explore other students' thoughts (resources) that may not have been discussed in previous research. This article focuses on the conceptual analysis of resources, namely the ideas they use in solving problems related to work-energy issues. This research aims to identify the resources used by physics students in work-energy reasoning as a work to explore students' new thoughts that have not been discussed in previous research. The research was conducted on 92 new physics department students in 2023 who took Basic Physics I lectures. Before the test was given, the lecturer gave a short review of the work-energy theorem to remind them of the knowledge they had learned in high school. The results of the research reveal that the resources that are widely used by students are (1) the concept of work in physics which is associated with the understanding of work in everyday contexts, namely as work/work/work, (2) in reasoning about motion phenomena involving potential energy and kinetic energy for students. directly apply the principle of conservation of mechanical energy. It is hoped that these findings will be useful input for lecturers in designing lectures on the topic of work-energy theorem based on resource theory or knowledge in pieces.